THE EFFECT OF DIFFERENT TEACHING SYSTEMS IN LEARNING RHYTHMIC GYMNASTICS APPARATUS MOTOR SKILLS - Despoina Τsopani; George Dallas; Niki Tasika; Amalia Tinto (Science of Gymnastics Journal)
The purpose of this study was to examine which of the two teaching systems, the Current Teaching System (CTS) and the Serial Organization System (SOS), is more effective in the learning rhythmic gymnastics skills in this novice (basic) level of students. The sample that consisted of 84 novices female students of physical education of Athens, aged 18-20 years old (19.02±0.77) who volunteered to participate in this study separated in two groups (n1=39, n2=43). At first, a pre test wad done to ascertain the initial level of performance and a post test after the end of practice in order to assess the effectiveness of these two teaching methods. All the experimental skills were evaluated by two teachers of University who were also official judges in the sport of Rhythmic Gymnastics. All participants took place in a nine weeks intervention program, 2 times per week for 90 minutes in each session (teaching unit). According to the results, although there was not a group effect in the pre test in each apparatus (p>.05), in the post test there was significant group effect in the total number of examined skills (p<.05). Further, there was a significant group effect between the two measurements in the total number of skills in each apparatus of ribbon (p<.05), rope and clubs (p<.001). Furthermore, it has to be stressed that the SOS had higher scores in the majority of examined skills in post test. Conclusively, SOS is more effective than CTS in case of learning Rhythmic Gymnastics skills according to the position of body and apparatus, especially in these cases where the parameters of implementation of exercise are not altered.